Peculiarities of the Pregnancy in Women with Hepatobiliary System Pathology - Guljakhan S. Babadjanova1, Mukhayo D. Abdurazakova2, Gulnara M. Nigmatova3, Dildora A. Ayupova4, Dil (Institute of Medico-legal Publications Pvt Ltd, 2020)
During pregnancy, there is a significant restructuring of various organs and systems, including liverfunctions. Due to the increase in circulating blood volume, most indicators of liver function may differ fromtheir level in non-pregnant women. In the liver of pregnant women, the synthesis of a large class of proteins(excluding immunoglobulins), fibrinogen, prothrombin, blood coagulation factors (V, VII, X, XI, XII, XIII),fibrinolytic factors (antithrombin III, proteins C and S) increases. Hepatic enzymes (serum transaminases,?-glutamyltranspeptidase), as well as the bilirubin content do not change during the physiological course ofpregnancy1.